Implementing early infant diagnosis of HIV infection at the primary care level: experiences and challenges in Malawi - Queen Dube; Anna Dow; Chawanangwa Chirambo; Jill Lebov; Lyson Tenthani; Michael Moore; Robert S Heyderman; Annelies Van Rie (The World Health Organization, 2012)
PROBLEM: Malawi's national guidelines recommend that infants exposed to the human immunodeficiency virus (HIV) be tested at 6 weeks of age. Rollout of services for early infant diagnosis has been limited and has resulted in the initiation of antiretroviral therapy (ART) in very few infants. APPROACH: An early infant diagnosis programme was launched. It included education of pregnant women on infant testing, community sensitization, free infant testing at 6 weeks of age, active tracing of HIV-positive infants and referral for treatment and care. LOCAL SETTING: The programme was established in two primary care facilities in Blantyre, Malawi. RELEVANT CHANGES: Of 1214 HIV-exposed infants, 71.6% presented for early diagnosis, and 14.5% of those who presented tested positive for HIV. Further testing of 103 of these 126 apparently HIV-positive infants confirmed infection in 88; the other 15 results were false positives. The initial polymerase chain reaction testing of dried blood spots had a positive predictive value (PPV) of 85.4%. Despite active tracing, only 87.3% (110/126) of the mothers of infants who initially tested positive were told their infants' test results. ART was initiated in 58% of the infants with confirmed HIV infection. LESSONS LEARNT: Early infant diagnosis of HIV infection at the primary care level in a resource-poor setting is challenging. Many children in the HIV diagnosis and treatment programme were lost to follow-up at various stages. Diagnostic tools with higher PPV and point-of-care capacity and better infrastructures for administering ART are needed to improve the management of HIV-exposed and HIV-infected infants.